IDENTIFICATION OF MISCONCEPTION IN NERVOUS SYSTEM SUBMATERIAL USING THREE-TIER MULTIPLE CHOICE DIAGNOSTIC TEST - Dyanti, Okta Prisma; Raharjo, Raharjo (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2018)
The nervous system is a part of biology lesson contain various physiological mechanisms that allow students Â misconceptions. The purpose of this research was describing studentâ€™s misconception profile and the cause of misconception using three-tier multiple choice diagnostic test. The type of the reseach was descriptive research with quantitative analysis. The research subjects were 60 students of XI IPA 1, IPA 2, and IPA 3 of SMA Negeri 16, biology teacher, and the learning material. Three-tier test was used for analysing student misconceptions of nervous system materials. The results of the research showed that the students' misconception profile was 41.14% on the eight topics of the nervous system submaterial with the highest misconception on the topic of neuron types and the function was 47.50%. Misconceptions were caused by the students, teacher, learning book, context, and learning method. Keywords : misconception, three-tier test, nervous system.